Efectos jurídicos de la subsanación voluntaria como atenuante: discordancia entre el nuevo Reglamento de la Autoridad Nacional de Control del Ministerio Público y el TUO de la Ley 27444 - Ticse Traverzo, Marlene Carmen (2025)
This qualitative research analyzes the legal effects of regulating voluntary remediation as a mitigating factor in the new Regulation of the National Control Authority of the Public Ministry (ANC-MP), which contradicts the Unified Text of Law No. 27444. Using a qualitative, descriptive case study design based on six interviews with magistrates of decentralized ANC-MP offices, the study found that while the Law recognizes voluntary remediation as an exemption, the Regulation limits it to a mitigating factor, generating legal uncertainty, administrative overload, and potential litigation. Most participants agreed that the Regulation should be aligned with the Law to strengthen legal security, administrative efficiency, and the preventive function of sanctioning law.